TRANSFORMASI STRATEGI BISNIS RUMAH SAKIT MELALUI HOSPITAL MARKETING 5.0, CUSTOMER VALUE, DAN CORE MARKETING CONCEPT: Systematic Review: Transformation Of Hospital Business Strategy Through Hospital Marketing 5.0, Customer Value, And Core Marketing Concept - Pramagistra, Latesia; Dhartono, Joanie DewiJanti; Fadillah, Listiana Nur; Yanuarti, Lita; Jumrah; Rohendi (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2025)
Introduction: Digital transformation has reshaped traditional marketing into a more personalized, predictive, and customer value–oriented approach. In the hospital industry, where service demand and patient expectations continue to rise, Marketing 5.0 provides a strategic framework that integrates technology with human-centered values. This study examines how Marketing 5.0, customer value, and core marketing principles influence the transformation of small business strategies in the digital era. Methods: A systematic literature review was conducted by analyzing ten peer-reviewed journals focusing on Industry 5.0, healthcare marketing, Marketing 5.0, and strategies for small enterprises. Results: Findings indicate that Marketing 5.0, supported by artificial intelligence (AI), the Internet of Things (IoT), and data analytics, transforms key marketing elements. “Product” shifts toward intelligent and personalized services, “price” becomes more dynamic and transparent, “place” integrates offline and online channels (omnichannel), and “promotion” evolves into more interactive and targeted communication. These changes foster the creation of broader customer value that includes not only clinical outcomes but also satisfaction, loyalty, and convenience. Discussion: Marketing 5.0 enables hospitals, especially small enterprises, to optimize operations while strengthening competitiveness. By emphasizing personalization, efficiency, and empathetic patient experiences, it positions healthcare providers to adapt effectively to digital transformation. Latar Belakang: Transformasi digital telah mengubah paradigma pemasaran tradisional menjadi pendekatan yang lebih personal, prediktif, dan berorientasi pada nilai pelanggan. Di industri rumah sakit, dimana kepuasan pelanggan dan penjualan terus meningkat, Marketing 5.0 menawarkan alat strategis revolusioner. Tujuan tinjauan literatur sistematis ini adalah menganalisis bagaimana konsep Pemasaran 5.0, nilai pelanggan, dan penerapan konsep pemasaran inti di era digital telah mengubah strategi bisnis untuk usaha kecil. Metode: Studi ini dilakukan dengan menganalisis sepuluh jurnal ilmiah yang membahas Industri 5.0, pemasaran kesehatan, Pemasaran 5.0, dan strategi bisnis untuk usaha kecil. Hasil dan analisis: Dengan menggunakan AI, IoT, dan analisis data, Marketing 5.0 mengubah setiap aspek desain interior rumah. Konsep “produk” merevolusi layanan yang pintar dan terpersonal, “harga” menjadi lebih dinamis dan transparan, “tempat” menggabungkan offline dan online (omnichannel), dan “promosi” menjadi lebih interaktif dan terarah. Transformasi ini memungkinkan terciptanya “nilai pelanggan” yang lebih komprehensif, tidak hanya mencakup hasil klinis tetapi juga kepuasan pelanggan, loyalitas, dan kenyamanan. Kesimpulan: Marketing 5.0, yang didukung oleh teknologi seperti kecerdasan buatan (AI), Internet of Things (IoT), dan analisis big data, berfokus pada penciptaan nilai pelanggan yang unik melalui personalisasi, efisiensi, dan pengalaman pasien yang empati. Transformasi ini tidak hanya mengoptimalkan operasional rumah sakit, tetapi juga memperkuat daya saing yang didasarkan pada nilai inti teknologi dan kemanusiaan.